Inovasi Pembelajaran: Pembuatan Konten Digital Arab-Inggris untuk Meningkatkan Keterampilan Bahasa - Very Erawanto; Nudya Kuntum Khoirel Abidah; Hikmawati, Rosyidatul; Yusri Fajar (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Arabic-English skills are the ability to master a language other than the mother tongue. The ability is very important in the era of globalization because there are many jobs require it. Digital content is material created digitally such as videos, podcasts, articles, and so on. Creating digital content, especially videos, is an effective way to improve foreign language skills, because it will encourage someone to use the language they have learned. Currently, video is one of the digital content that is of great interest to teenagers. Coaching in creating digital content is carried out by accompanying and guiding students to create good and correct digital content. This assistance and guidance includes the use of correct grammar, use of appropriate vocabulary, as well as feedback or feedback on the content that has been created. It is hoped that with this coaching, participants will be able to improve their foreign language skills and hone their skills in creating digital content. In addition, it is also expected to increase the participants' interest and motivation to continue learning and develop foreign language skills. Keywords: foreign language skills; digital content; video